Reservoir of Bacterial Exotoxin Genes in the Environment - Veronica Casas; Joseph Magbanua; Gerico Sobrepeña; Scott T. Kelley; Stanley R. Maloy (International Journal of Microbiology)
Many bacteria produce secreted virulence factors called exotoxins. Exotoxins are often encoded by mobile genetic elements, including bacteriophage (phage). Phage can transfer genetic information to the bacteria they infect. When a phage transfers virulence genes to an avirulent bacterium, the bacterium can acquire the ability to cause disease. It is important to understand the role played by the phage that carry these genes in the evolution of pathogens. This is the first report of an environmental reservoir of a bacterial exotoxin gene in an atypical host. Screening bacterial isolates from the environment via PCR identified an isolate with a DNA sequence >95% identical to the Staphylococcus aureus enterotoxin A gene (sea). 16S DNA sequence comparisons and growth studies identified the environmental isolate as a psychrophilic Pseudomonas spp. The results indicate that the sea gene is present in an alternative bacterial host, providing the first evidence for an environmental pool of exotoxin genes in bacteria.